Strategi Blended Learning Dalam Pengembangan Kompetensi ASN: Redefinisi Dan Implementasi Di Lembaga Administrasi Negara - Mariesta, Adinda; Yuni Astuti, Erni; Handayani, Nida (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2024)
The purpose of this study is to examine the strategy of implementing the blended learning model for the development of ASN competencies conducted by the National Institute of Public Administration (Lembaga Administrasi Negara). In this study, the method used is a qualitative approach with the Systematic Literature Review (SLR) method. SLR is a systematic literature review aimed at identifying, evaluating, and interpreting the main research findings (Barricelli et al., 2019). Based on the results of study, the National Institute of Public Administration has implemented ASN competency development using the blended learning model. In accordance with LAN Regulation Number 1 of 2021, Article 7, Paragraph (1), Letter b, blended learning is implemented through three components of learning: independent training, distance learning, and classical learning at the basic CPNS training site.Based on these findings, it can be concluded that the development of ASN competencies using the blended learning model can be applied to the Basic CPNS Training in 2021 and future Basic CPNS Trainings, as it is considered to have an impact on ASN performance, budget efficiency, and the effectiveness of learning.